The Precision Of The Giving Of The Drug Based On Service Identifikation Of Patien Compliance At â€œDarmayuâ€ General Hospital Ponorogo - Ellina, Agusta Dian; Suwarno, Suwarno; Fawzi, Alfian (Journal Of Nursing Practice, 2018)
The research was distributed by drug services granting conditions up to this moment there are still many problems. As for the problem of the research is "whether the compliance of nurses in identifying influence on accuracy in the service of dispensing". Aim of this research is to know the level of compliance officers perform identification before providing the service of medicine, knowing compliance do identification relationship and analyze correctness of granting of service remedy with precision identification in "Darmayu" general hospital Ponorogo. In this study data collected through questionnaire method against 40 people the respondents admitted in "Darmayu" general hospital using the accidental method, Ponorogo for knowing the responses of respondents to each variable. Then conducted an analysis of the data obtained in the form of quantitative analysis. Quantitative analysis includes the test validity and reliability, as well as test the correlation of Phi. Of research results, data the respondents obtained shows that the level of accuracy of the perwat in the service of the drug still has not been fullest is demonstrated from 40 respondents, there were 22 stating the precision. Likewise, the level of compliance of nurses in conducting identification is still lacking, from 40 respondents, 14 respondents declared not obedient in doing identification. The results of the analysis of the compliance officers do get that the identification of the effect on the precision in the service of medicine. Hypothesis testing using the test correlation of Phi showed that independent variables examined is proven to significantly affect the dependent variable. Patient safety incidents can be prevented by the presence of the nurse in conducting compliance identification as well as precision in running the SOP. Sosiaisasi and high awareness of nurses on the importance of obedience and compliance in carrying out procedures will greatly affect the success of a service to patients at home sick.